Studies on Hanguana (Commelinales, Hanguanaceae) for Sunda II: Five new forest species from Peninsular Malaysia and recircumscription of Hanguana malayana - Siti Nurfazilah, Bt Abdul Rahman; Ahmad Sofiman, Othman; Mohd Fahmi, Bin Abu Bakar; Boyce, P.C (BGBM Berlin-Dahlem., 2010)
Field work in Peninsular Malaysia as part of the first author's research into relationships and evolutionary polarity between Hanguana malayana, a widespread freshwater helophyte, and the numerous and mostly undescribed Sundaic forest species has to date resulted in the collection of five distinctive novel forest-dwelling Hanguana species. These are described here and figured in colour. Increased understanding of these and other forest species of Hanguana has enabled a concise delimitation of the taxonomically long-obfuscated colonial helophytic H. malayana, and this is here presented, and the species figured. The current taxonomy of Hanguana is summarised, and a key to the so-far described Peninsular Malaysian species is provided.